Balancing scientific accuracy and participant burden: testing the impact of sampling intensity on diurnal cortisol indices. (2nd September 2016) - Hoyt, Lindsay Till; Ehrlich, Katherine B.; Cham, Heining; Adam, Emma K.
Abstract: Despite the increasing popularity of incorporating salivary cortisol measurement into health and social science research, relatively little empirical work has been conducted on the number of saliva samples across the day required to capture key features of the diurnal cortisol rhythm, such as the diurnal cortisol slope, the area under the curve (AUC), and the cortisol awakening response (CAR). The primary purpose of this study is to compare slope, AUC, and CAR measures obtained from an intensive sampling protocol with estimates from less intensive protocols, to identify sampling protocols with minimal participant burden that still provide reasonably accurate assessment of each of these measures. Twenty-four healthy adults provided samples four times in the first hour awake, and then every hour throughout the rest of the day until bedtime ( M = 17.8 samples/day; SD = 2.0), over two consecutive days ( N = 862 total samples). We compared measures calculated from this maximum intensity protocol to measures calculated from two to six sampling points per day. Overall, results show that salivary cortisol protocols with two fixed samples (waking and bedtime) and three additional daily samples, closely approximates the full cortisol decline (slope). Abbreviated sampling protocols of total cortisol exposure across the day (AUC), however, were not well approximated by reduced sampling protocols. CAR measures based on only two samples, including waking cortisol and a second sample measured at a fixed time point between 30 and 60 min after waking, provided a measure of the CAR that closely approximated CAR measures obtained from 3 or 4 sampling points.